EFFICACY OF ORAL VS VAGINAL MISOPROSTOL IN FIRST TRIMESTER MISSED MISCARRIAGE (The Research of Medical Science Review, 2024)
Background: First-trimester missed miscarriage is commonly managed with misoprostol, either orally or vaginally. While vaginal misoprostol is thought to be more effective, controversy exists regarding the comparison of oral versus vaginal forms, with inconsistent findings in the literature. Additionally, data on this issue in local population is scarce. This study was conducted to assess and compare the efficacy of oral and vaginal misoprostol in a local population. Objective: To compare the efficacy of misoprostol by vaginal and oral route, for the management of first trimester missed abortion. Duration: Six months.Methodology: A total of 140 patients with of patients with missed abortion, 18 to 45 years of age were included. Patients with signs of allergy to or C/I to misoprostol use, anemia, active lactation, bleeding disorder, deranged coagulation profile and infection were excluded. In group A, 400μg vaginal misoprostol was given, while in group B patients, 400μg oral misoprostol was done. All patients were monitored for vitals, vaginal bleeding and expulsion of POCs. Over the next 18-30 hours, complete, incomplete or no expulsion was documented. Results: The study sample consisted of 140 participants, with a mean age of 27.71 ± 4.31 years. The mean gestational age at the time of enrollment was 7.63 ± 2.35 weeks. In terms of parity, the mean was 3.29 ± 1.15. Both groups were statistically comparable with each other for all baseline variables, as indicated by the p-values greater than 0.05. In terms of efficacy, Group A demonstrated a higher success rate, with 65 participants (92.86%) achieving a successful outcome, compared to 53 participants. Stratification of efficacy between the groups based on age, gestational age, and parity revealed a consistent superiority of Group A over Group B across all subgroups. However, in certain subgroups, statistical significance could not be achieved due to the small sample sizes. Conclusion: The study demonstrated that vaginal misoprostol (Group A) was more effective than oral misoprostol (Group B) in the management of first-trimester missed miscarriage, with a significantly higher success rate observed in Group A. Stratification by age, gestational age, and parity consistently showed the superiority of vaginal misoprostol across all subgroups. However, statistical significance was not achieved in some subgroups due to small sample sizes. Overall, vaginal misoprostol appears to be a more effective treatment for missed miscarriage in the first trimester.